Avaliação dos escores de risco cardiovascular em pessoas vivendo com HIV/AIDS: comparação entre o DAD escore reduzido e escore de Framingham. - PRADO, Beatriz Freitas do (2023)
People living with HIV/AIDS may have endocrine-metabolic alterations such as dyslipidemia and diabetes mellitus, risk factors for cardiovascular events. Given the standardized use of cardiovascular tools that lack specificity for the aforementioned population, this research aimed to evaluate the association between risk factors and specific and non-specific cardiovascular risk calculators, Data Collection on Adverse Effects of Anti-HIV Drugs Cohort (DAD) Reduced Score and Framingham Score respectively. The study included people over 18 years of age, treated at the endocrinology outpatient clinic of the Tropical Medicine Center of the Federal University of Pará, in addition to collecting clinical and laboratory data relevant to the calculation of cardiovascular risk in the two calculators, and also collecting data to identify variables associated with cardiovascular risk such as the occurrence of metabolic syndrome by the criteria of NCEP-ATP3 and the International Diabetes Federation (IDF) and the presence of lipodystrophy. Ninety-four patients were included, including 51 men (mean 57.1 and standard deviation 11.8) and 43 women (mean 52.9 and standard deviation 12.2). It was observed that the Framingham Score, when compared to the Reduced DAD Score, underestimated patients at moderate cardiovascular risk, while the Reduced DAD Score, when compared to the Framingham Score, underestimated high-risk patients. As for the variables associated with cardiovascular risk, it was observed that the presence of lipodystrophy in 80 patients (85.1%) was related to a greater cardiovascular risk, while the presence of metabolic syndrome by NCEP ATP-III with 50 patients (53, 1%) and by the IDF 57 patients (60.6%) was associated with a high cardiovascular risk. It is concluded, then, that the use of two calculators should be considered in the management of these patients, considering the highest risk score for taking preventive measures, and the presence of lipodystrophy and metabolic syndrome should also be observed in order to optimize control of the cardiovascular risk in people living with HIV/AIDS.